Fluvastatin delays propagation of viral infection in isolated rat FDB myofibers but does not affect exocytic membrane trafficking. (27th July 2015) - Nevalainen, Mika; Metsikkö, Kalervo
Abstract We have utilized the enveloped viral model to study the effect of fluvastatin on membrane trafficking in isolated rat myofibers. Our immunofluorescence studies constantly showed that infections in myofibers, which were treated with fluvastatin prior and during the infection with either vesicular stomatitis virus (VSV) or influenza A virus, propagated more slowly than in control myofibers without drug treatment. Experiments with a virus expressing Dad1 tagged with green fluorescent protein (GFP‐Dad1) showed that fluvastatin did not affect its distribution within the ER/SR network and immunofluorescence staining for GM130 did not show any marked effect on the structure of the Golgi components. Furthermore, fluvastatin did not inhibit trafficking of the chimeric transport marker VSV temperature sensitive G protein (tsG‐GFP) from the ER to the Golgi. We next subjected VSV infected myofibers for pulse‐chase labeling experiments and found that fluvastatin did not slow down the ER‐to‐Golgi trafficking or Golgi to plasma membrane trafficking of the viral glycoprotein. These studies show that fluvastatin inhibited the propagation of viral infection in skeletal myofibers but no adverse effect on the exocytic trafficking could be demonstrated. These results suggest that other effects of statins rather than inhibition of ER‐to‐Golgi trafficking might be behind the myotoxic effects of the statins.